A study on the Chinese translation Strategies of Arabic Proverbs from the Perspective of Cultural Translation - Linxian, Yuan (Arab Journal for Sciences and Research Publishing, 2023)
Proverbs are the essence of a language and have strong national cultural color. The translation of proverbs is not only a linguistic transformation, but also a cultural exchange. This paper discusses the meaning of cultural translation and points out that the essence of cultural translation is to reflect the cultural information carried by language. Cultural translation and foreignization translation have similar purposes. This paper expounds the cultural commonness and cultural individuality refracted by Arab proverbs with abundant examples. On this basis, the paper points out that the proper translation strategies should be chosen according to the cultural characteristics of the Arabic proverbs.
Keywords: Arabic proverbs; cultural translation; translation strategies